Influences of Neck and/or Wrist Pain on Hand Grip Strength of Industrial Quality Proofing Workers - Bettina Wollesen; Julia Gräf; Nils Schumacher; Gianluca Meyer; Matthias Wanstrath; Christian Feldhaus; Kerstin Luedtke; Klaus Mattes (Elsevier, 2020)
Background: The aim of this study was to analyze the interaction between neck and/or wrist pain and hand grip strength (HGS) and to investigate factors (age, sex, neck disorders, and carpal tunnel syndrome) influencing the HGS of industrial quality proofing workers (N = 145). Methods: Standardized questionnaires [Neck Disability Index (NDI), Boston Carpal Tunnel Questionnaire] were used to evaluate existing neck and/or wrist pain. HGS measurements were performed in different wrist positions. Results: Significant differences between participants with and without neck pain were found in different wrist positions, in neutral wrist position right [without neck pain (n = 48) 46.34 (43.39 - 49.30); with neck pain (n = 97) 38.46 (36.20 - 40.72), F(1,144) = 16.82, p < 0.001, ŋp2 = 0.11] and left [without neck pain 44.06 (41.19 - 46.94); with neck pain 37.36 (35.13 - 39.58), F(1,144) = 12.70, p < 0.001, ŋp2 = 0.08]. A significant difference between participants with and without wrist pain was found for neutral wrist position right [without wrist pain (n = 105) 42.53 (40.37 - 44.70); with wrist pain (n = 40) 37.24 (33.56 - 40.91), F(1,144) = 6.41, p = 0.01, ŋp2 = 0.04]. Regression analysis showed significant results especially for steps two (age and weight, NDI) and three (age and weight, NDI, Boston Carpal Tunnel Questionnaire) for neutral position right (R2 = 0.355, R2 = 0.357, respectively). Conclusion: Neck pain has an impact on HGS but should be evaluated in consideration of age and sex.